2006
DOI: 10.1590/s0103-50532006000700013
|View full text |Cite
|
Sign up to set email alerts
|

Dereplication of glycosides from Sapindus saponaria using liquid chromatography-mass spectrometry

Abstract: Frutos de Sapindus saponaria (Sapindaceae), uma planta amplamente distribuída nos trópicos, foram coletados a cada trinta dias, durante seis meses. Estudos usando cromatografia a líquido com detecção por UV e EM (CLAE/UV/ESI-EM) e fragmentações por EM/EM, mostraram que os principais glicosídeos presentes nesses frutos são saponinas (SAP) derivadas dos triterpenos hederagenina e ácido oleanólico, e oligoglicosídeos de sesquiterpenos acíclicos (ASOGs). Usando esses métodos de análise, foram detectados até trinta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
3
19
0
2
Order By: Relevance
“…2 Alkaline hydrolysis of these natural glycosides produced simplified mixtures of compounds formed of only four SAPs and five ASOGs. Preparative scale HPLC separation of the SAP fraction let to isolation of pure saponin 1, which was characterized as 3-O-( -D-xylopyranosyl)-(1 3)--L-rhamnopyranosyl-(1 2)--L-arabinopyranosylhederagenin by comparison of both MS and NMR spectra with those published by Grover and co-workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Alkaline hydrolysis of these natural glycosides produced simplified mixtures of compounds formed of only four SAPs and five ASOGs. Preparative scale HPLC separation of the SAP fraction let to isolation of pure saponin 1, which was characterized as 3-O-( -D-xylopyranosyl)-(1 3)--L-rhamnopyranosyl-(1 2)--L-arabinopyranosylhederagenin by comparison of both MS and NMR spectra with those published by Grover and co-workers.…”
Section: Resultsmentioning
confidence: 99%
“…1 Studying the glycoside composition of this soap by means of mass spectrometry coupled with liquid chromatography (LC-MS), it was found that those fruits accumulate on their pericarp huge amounts of monodesmosidic triterpene (SAPs) and bisdesmosidic sesquiterpene (acyclic sesquiterpene oligoglycosides, ASOGs) acetylated saponins. 2 Saponins are usually referred as antifungal and antibacterial compounds, being the monodesmosidic the most active ones. 3,4 These compounds form a group of chemical weapons used by plants in the fight against fungi, and the protection against pathogenic microbes is probably their natural role in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Hederagenin derived saponins (SAPs) and acyclic sesquiterpene oligoglycosides (ASOGs) used as substrates in these experiments were obtained from the host plant (Murgu and Rodrigues-Filho 2006); oleanolic acid was isolated from flowers of Eugenia triflorida, which produces this compound in great yields; a commercial sweeter (Stevita TM ) containing 3% stevioside on its formula was also used. The fungus was cultivated the same way described above but with the medium containing each of the substrate at a concentration of 5 mg for each 100 ml of liquid medium.…”
Section: Biotransformation Experiments and Chemical Analysismentioning
confidence: 99%
“…Studying the glycoside composition of the soap produced by S. saponaria, using mass spectrometry coupled with liquid chromatography, we found that the fruit accumulate on its pericarp huge amounts of monodesmosidic triterpene and bisdesmosidic sesquiterpene saponins (e.g. 1 and 2, respectively) (Murgu and Rodrigues-Filho 2006), which where found as a mixture of naturally non-regiosselective acetylated compounds. Saponins are usually referred as antifungal and antibacterial compounds, being the monodesmosidic ones the most actives (Gruiz 1996;Morrossey et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Using these methods of analysis, 30 saponins and 63 acyclic sesquiterpene oligoglycosides have been detected (Murgu & Rodrigues-Filho 2006;Pelegrini et al 2008). Saponins display diverse behaviors, such as molluscicidal, and piscicidal, anti-infl ammatory, analgesic, expectorant, antioxidant, antiviral, antibacterial and antifungal activity (Sparg et al 2004).…”
Section: Introductionmentioning
confidence: 99%